Diagnostic Value of Vaginal Discharge, Wet Mount and Vaginal pH – An Update on the Basics of Gynecologic Infectiology - Frobenius, W.; Bogdan, C. (Geburtshilfe und Frauenheilkunde, 2015)
The majority of uncomplicated vulvovaginal complaints (e.g. bacterial vaginosis, vulvovaginal candidiasis, trichomoniasis) can be detected with uncomplicated basic infectiological tests and can usually be treated effectively without requiring further diagnostic procedures. Tests include measurement of vaginal pH, preparation and assessment of wet mount slides prepared from vaginal or cervical discharge, and the correct clinical and microbiological classification of findings. In Germany, at least in recent years, this has not been sufficiently taught or practiced. As new regulations on specialist gynecologic training in Germany are currently being drawn up, this overview provides basic information on gynecologic infectiology and summarizes clinically relevant aspects of recent microbiological findings on the physiology and pathology of vaginal flora. The clinical signs and symptoms of aerobic vaginitis, the pathogenesis of which is still not completely understood, are also reviewed. Finally, the symptoms, indications and risk factors for pelvic inflammatory disease (PID) are presented. In contrast to the above-listed infections, PID requires immediate culture of the pathogen from samples (e.g. obtained by laparoscopy) with microbiological diagnostic procedures carried out by specialist laboratories. A schematic summary of all pathologies discussed here is presented.
Keywords: bacterial vaginosis; vulvovaginal candidiasis; trichomoniasis; pelvic inflammatory disease; vaginal pH